2009
DOI: 10.1001/archgenpsychiatry.2009.81
|View full text |Cite
|
Sign up to set email alerts
|

National Patterns in Antidepressant Medication Treatment

Abstract: From 1996 to 2005, there was a marked and broad expansion in antidepressant treatment in the United States, with persisting low rates of treatment among racial/ethnic minorities. During this period, individuals treated with antidepressants became more likely to also receive treatment with antipsychotic medications and less likely to undergo psychotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

41
468
3
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 674 publications
(523 citation statements)
references
References 55 publications
41
468
3
11
Order By: Relevance
“…Our question about drug use during most of the previous 4 weeks would not include short‐duration users, but this exclusion is an advantage for studying of the effects of psychotropic drugs on VTE risk. That a sizeable proportion of women who reported taking an antidepressant did not report being treated for anxiety or depression, and similarly that not all women who reported they were being treated for depression or anxiety reported use of antidepressants, is consistent with previous US and UK research 26, 27, 28…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our question about drug use during most of the previous 4 weeks would not include short‐duration users, but this exclusion is an advantage for studying of the effects of psychotropic drugs on VTE risk. That a sizeable proportion of women who reported taking an antidepressant did not report being treated for anxiety or depression, and similarly that not all women who reported they were being treated for depression or anxiety reported use of antidepressants, is consistent with previous US and UK research 26, 27, 28…”
Section: Discussionsupporting
confidence: 83%
“…Antidepressants are used to treat depression, anxiety, and various pain‐related conditions, and the utilization of these drugs has been increasing in the United Kingdom, United States, and elsewhere 27, 36, 37. National quality standards in the United Kingdom, which recommend that people who may have depression are assessed to determine the severity of the condition and identify appropriate treatments,38 and a national objective to increase the proportion of US adults with major depressive disorders who receive treatment,39 may lead to further increases in antidepressant use.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies in other countries, lower income or lower educational attainment was associated with a lower prevalence of depression treatment, or there was no association [22][23][24][25][26]. In the present study, however, the lowestincome quintile showed the highest rate of depression treatment among respondents with psychological distress.…”
Section: Discussioncontrasting
confidence: 72%
“…In the present study, however, the lowestincome quintile showed the highest rate of depression treatment among respondents with psychological distress. Although there is generally a barrier to medical treatment for the lower-income population, particularly in the United States, which lacks nationalized health care [24,25], in Japan this barrier appears to be relatively low due to the universal coverage of health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Although depression is a significant health problem in the United States and antidepressants are heavily prescribed (2), the mechanism of action for these drugs is not understood. Further, nearly a third of those treated with these drugs do not achieve remission of their depression (3).…”
mentioning
confidence: 99%